Application of Wedges for the Reduction of the Space and Time-Dependent Harmonic Content in Squirrel-Cage Induction Motors. (29th December 2013) - Gyftakis, Konstantinos N.; Panagiotou, Panagiotis A.; Kappatou, Joya C.
Abstract : The influence of the semimagnetic stator wedges of different sizes on the electromagnetic characteristics and the behavior of the induction motor is investigated. The study will be carried out with both analytical calculations and FEM analysis. The analytical calculations will take into account the stator and rotor slots, as well as the iron core saturation in order to study the spatial and time-dependent harmonic content of the air-gap magnetic flux density and electromagnetic torque. The size of the wedge plays an important role as it determines the tooth tips saturation, the high harmonic content of the air-gap magnetic flux density, and the electromagnetic characteristics of the induction motor.